The puzzling story of flare inactive ultra fast rotating M dwarfs – I. Exploring their magnetic fields. Issue 1 (21st February 2022) - Doyle, Lauren; Bagnulo, Stefano; Ramsay, Gavin; Doyle, J Gerry; Hakala, Pasi
ABSTRACT: Stars which are rapidly rotating are expected to show high levels of activity according to the activity–rotation relation. However, previous TESS studies have found ultra fast rotating (UFR) M dwarfs with periods less than 1 d displaying low levels of flaring activity. As a result, in this study, we utilize VLT/FORS2 spectro-polarimetric data of 10 M dwarf UFR stars between spectral types ∼M2–M6 all with P rot < 1, to detect the presence of a magnetic field. We divide our sample into rotation period bins of equal size, with one star having many more flares in the TESS light curve than the other. We also provide an analysis of the long-term variability within our sample using TESS light curves taken during Cycles 1 and 3 (up to 3 yr apart). We identify 605 flares from our sample which have energies between 2.0 × 10 31 and 5.4 × 10 34 erg. Although we find no significant difference in the flare rate between the Cycles, two of our targets display changes in their light-curve morphology, potentially caused by a difference in the spot distribution. Overall, we find five stars (50 per cent) in our sample have a detectable magnetic field with strengths ∼1–2 kG. Of these five, four were the more flare active stars within the period bins with one being the less flare active star. It would appear the magnetic field strength may not be the answer to the lack of flaring activity and supersaturation or magnetic field configuration may play a role. However, it is clear the relationship between rotation and activity is more complex than a steady decrease over time.